The complete mitochondrial genome of Hemigrapsus penicillatus (De Haan, 1835) (Decapoda, Varunidae) - Karagozlu, Mustafa Zafer (Mitochondrial DNA B Resour, 2018)
Hemigrapsus penicillatus is a small grapsoid crab which is found in Japan, Taiwan, Korea, and China coasts. In this study a complete mitogenome of Korean H. penicillatus was analyzed and phylogenetic relationships in the family Varunidae were investigated. The mitogenome size is 16,486 bp with 34.1% A, 18.1% C, 11.4% G, and 36.4% T nucleotide distributions. Genome structure and gene orientations are identical with previous records from the family and mitochondrial protein-coding gene based phylogenetic tree suggested that the closest species to H. penicillatus is H. sanguineus. This is the second complete mitogenome record from the genus Hemigrapsus and the first record for the species.